2013
DOI: 10.6028/nist.sp.1138
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for a More Sustainable Concrete Infrastructure : A Vision for Developing a Comprehensive Description of Cement Hydration Kinetics

Abstract: Pav i ng t he W ay f or a Mor e S u s t ai nabl e C onc r et e I nf r as t r u c t u r e A V i s i o n f o r D e v e l o p i n g a C o m p r e h e n s i v e D e s c r i p t i o n o f C e m e n t H y d r a t i o n K i n e t i c s National Institute of Standards and Technology Patrick D. Gallagher, Under Secretary of Commerce for Standards and Technology and DirectorCertain commercial entities, equipment, or materials may be identified in this document in order to describe an experimental procedure or concept ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, accurately predicting the rate of change in the microstructure has proven to be extremely difficult, in part because the initial binder material is inherently variable in its composition and reactivity but primarily because there are significant gaps in the quantitative understanding of the basic mechanisms that govern the reactions of the solid binder components with water. Any microstructural model rooted in the basic physics and chemistry of materials will require input of the details of the binder’s starting mineralogical composition, particle size distribution, and basic thermodynamic and kinetic properties of the reactions being simulated, including the dissolution rate laws and constants of individual cementitious minerals. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accurately predicting the rate of change in the microstructure has proven to be extremely difficult, in part because the initial binder material is inherently variable in its composition and reactivity but primarily because there are significant gaps in the quantitative understanding of the basic mechanisms that govern the reactions of the solid binder components with water. Any microstructural model rooted in the basic physics and chemistry of materials will require input of the details of the binder’s starting mineralogical composition, particle size distribution, and basic thermodynamic and kinetic properties of the reactions being simulated, including the dissolution rate laws and constants of individual cementitious minerals. , …”
Section: Introductionmentioning
confidence: 99%
“…Any microstructural model rooted in the basic physics and chemistry of materials will require input of the details of the binder's starting mineralogical composition, particle size distribution, and basic thermodynamic and kinetic properties of the reactions being simulated, including the dissolution rate laws and constants of individual cementitious minerals. 1,2 Substantial progress has been made in characterizing the fundamental dissolution rates and mechanisms of some minerals, especially calcite and gypsum, which are minority components of portland cement. Much of the recent progress has involved monitoring nanoscale changes in surface topography with vertical scanning interferometry (VSI) and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of hydration in controlling concrete properties such as strength, permeability, and durability was reviewed in a joint publication by the National Institute of Standards and Technology (NIST) and Federal Highway Administration (FHWA). 35 The study of Shin et al 10 on the effect of internal curing on ASR expansion in mortar suggested three possible beneficial elements that potentially reduce damage from ASR in the mortars as a result of the LWA 10 : 1) increase cement hydration and reduced interfacial transition zones (ITZ); the rate of fluid ingress and movement is reduced, which may in turn reduces the rate of ASR reaction; 2) the dilution effect provided by the replacement of LWA for a portion of the reactive particles in the fine aggregate reduces the potential for a portion of the ASR expansion; and 3) extra pores provided by LWA may provide available deposit sites for the gel in such way to minimize the pressure due to expansion.…”
Section: Internal Curing As Mitigation To Minimize Asr Damage In Concmentioning
confidence: 99%